Anther culture of local upland rice varieties from East Kalimantan: effect of panicle cold pre-treatment and putrescine enriched medium - NURHASANAH NURHASANAH; ANANDA N. PRATAMA; WIDI SUNARYO (Biodiversitas Journal of Biological Diversity, 2016)
Nurhasanah, Pratama AN, Sunaryo W. 2016. Anther culture of local upland rice varieties from East Kalimantan: effect ofpanicle cold pre-treatment and putrescine enriched medium. Biodiversitas 17: 148-153. Anther culture has been evaluated as aneffective method for homozygous plant production which is very important for the hybrid breeding program in rice. Low number ofgreen plantlets is a main obstacle in the application of this technique. Culture conditions increasing anther culture efficiency can beapplied to solve this problem especially for low regeneration frequency. This study aimed to investigate the effect of panicle cold pretreatment and the addition of putrescine into culture medium to theanther culturability of local upland rice varieties originated from East Kalimantan. Two cold pretreatment times, 8 and 10 days, at 4°C and anther culture medium with and without putrescine were examined in this research. The result showed that cold incubation time effect was a genotype-dependent in influencing the ability of rice microspores to develop into callus and green plantlet regeneration. The longer cold incubation time, 10 days, resulted in the highest number of callus, plantlet as well as green plantlets in Serai Gunung cultivar but the opposite result was found in Geragai cultivar. The effect of putrescine addition in the culture medium was also observed as a genotyped-dependent. It can either increase number of calli, plantlets and green plantlets or decrease them on a specific genotype.